Educational Conflict: A Management Perspective To Resolve Educational Violence in Islamic Boarding School - Halid, Ahmad; Hidayah, Anis Rofi; Nursyamsiyah, Siti; bin Jali, Hasan (Universitas Negeri Jakarta, 2025)
Background In the dynamics of general education and Islamic education, there will definitely be conflicts, both individual conflicts and group conflicts. In cases of conflict, the leader of the Islamic boarding school must understand the conflict management that will be carried out because it will greatly influence and have a positive or negative impact on the progress of the Islamic boarding school. Purpose The purpose of this study is to analyze educational conflict in Islamic boarding schools. Design/method/approach The method using a qualitative approach and using observation, documentation and interview data collection methods and using library data both offline and online and access in mass media such as books, google, newspapers, TV news, magazines, online journal articles. Results In managing human conflict in general by avoiding problems. This avoidance is based on fear of disputes and paralysis of function. The characteristic is the tendency to reject thoughts and avoid problems. Second, Approaching the problem and trying to find a solution. This characteristic is based on optimism and is more functional. violence is any act against a child that results in physical misery or suffering. Contribution/value This study provides strategies to stakeholders in educational institutions in handling conflicts and utilizing the conflict to be positive and advance educational institutions.